Collective action and property rights for poverty reduction: Insights from Africa and Asia - Mwangi, E; Markelova, H.; Meinzen-Dick, Ruth S. (2012)
Collective action and property rights are two institutions that can significantly contribute to poverty reduction. Collective action aids in the efficient use and protection of natural resources and helps the poor secure land rights by advocating for themselves and their best interests. Secure individual or communal property rights to natural resources, such as land, water, trees, livestock, fish, and genetic resources, are vital to rural people’s livelihoods because they ensure income and provide incentives to invest in productive technologies and sustainably manage resources.